Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1016/j.hrtlng.2004.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of successful heart failure self-care maintenance in the first three months after hospitalization

Abstract: Elderly men and those with fewer comorbid illnesses were most successful at HF self-care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
109
7
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(127 citation statements)
references
References 31 publications
8
109
7
1
Order By: Relevance
“…24. recent studies showing a correlation between social support and self-care, as well as between age and self-care in patients with heart failure. 16,28,29 Nevertheless, several limitations of our study should be noted: 1) Because of the cross-sectional design of the present study, the direction of causality in the relationship between self-care and depression remains unclear. 2) As mentioned above, selfcare of our patients with CHF is self-reported and possibly differs from actual behavior in everyday life.…”
Section: Discussionmentioning
confidence: 83%
“…24. recent studies showing a correlation between social support and self-care, as well as between age and self-care in patients with heart failure. 16,28,29 Nevertheless, several limitations of our study should be noted: 1) Because of the cross-sectional design of the present study, the direction of causality in the relationship between self-care and depression remains unclear. 2) As mentioned above, selfcare of our patients with CHF is self-reported and possibly differs from actual behavior in everyday life.…”
Section: Discussionmentioning
confidence: 83%
“…Eleven of the articles were rated as good quality, fifteen as fair quality (the articles are numbered according to quality score in Tables 2 and 4; studies numbered 1-11 are rated as good quality [18][19][20][21][22][23][24][25][26][27][28], and those numbered 12-26 are rated as fair quality [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]). Four articles were excluded due to a low quality score [44][45][46][47].…”
Section: Resultsmentioning
confidence: 99%
“…Although some studies used the term ''self-care'' [26,27,33,40,43], other studies used other terms, including ''self-management'' [18,32,39], ''adherence'' [35], ''compliance'' [20,29,36] and ''self-care specific behaviours'' [21]. In addition, eight articles reported results on self-care management [22,25,30,31,33,38,41,42] and ten on self-care maintenance [22,25,30,31,33,34,37,38,41,42]. …”
Section: Resultsmentioning
confidence: 99%
“…These studies have been fairly consistent in identifying female gender, 19,20 higher (worse) New York Heart Association (NYHA) functional class, lower education 11 and shorter illness duration 11,17,21 as determinants of poor self-care maintenance while the effects of age and comorbidity are unclear. Some studies have found that younger age is associated with poor self-care maintenance 18,19 but one study reported the contrary. 22 One study 18 found that fewer comorbid conditions were associated with poorer self-care but another one 11 found no relationship between comorbidity and self-care maintenance.…”
Section: Introductionmentioning
confidence: 93%